Morphology, characterization, and conversion of the corals Goniopora spp. and Porites cylindrica to hydroxyapatite - (:unkn) unknown (SPRINGER, 2019)
The aim of this study is to obtain pure natural hydroxyapatite (HAp) and tricalcium phosphate (TCP) from a Goniopora spp. and from hump coral (Porites cylindrica), both sourced from Australia. Due to the nature of the conversion process, commercial coralline HAp has retained coral or CaCO3, and the structure possesses both nano- and mesopores within the interpore trabeculae resulting in high dissolution rates. To overcome these limitations, a newly patented coral double-conversion technique has been developed. The current technique involves a two-stage application route where in the first-stage complete conversion of coral to pure HAp is achieved. In the second stage, a sol-gel-derived HAp nanocoating is directly applied to cover the meso- and nanopores within the intrapore material, while maintaining the large pores. Here, we specifically investigated the morphological changes and characterized these corals prior to and after conversion. For this purpose, four groups designated as C-0, C-1, C-2, and C-3 were used. C-0 is Porites, Goniopora, and cylindrica; the original coral is calcium carbonate with aragonite structure that contains proteins and polysaccharides. C-1 is coral cleaned under ultrasound in bleach diluted with water. C-2 is coral converted to hydroxyapatite (HAp) by hydrothermal treatment method at 200 degrees C under pressure in the presence of ammonium biphosphate. C-3 is obtained by coating C-2 with sol-gel alkoxide-derived nanohydroxyapatite to obtain a more bioactive osteoconductive material and improve mechanical properties. All groups were characterized by XRD, EDAX, DTA/TGA, and SEM. The results showed that the biaxial strengths of the C-2 and C-3 were significantly higher than the original coral. The work also showed the advantages of the hydrothermal conversion method and the effect of the nanocoating which is expected to improve the final bioactivity through microstructural changes of the surfaces.
Keywords: Corals; Aragonite; Natural bioceramics; Ultrasonication; Hydrothermal treatment